Pemanfaatan Teknologi Spasial pada Pemetaan Partisipatif Potensi Tanaman Aren: Penguatan Kelompok Tani Hutan Karya Baru Kabupaten Maros - Samsu, Andi Khairil A.; Hajar, Hajar; Ariandi, Rahmat; Nurnawati, Andi Ayu; Ardiansyah, Didit; Taufik, Taufik; Mukhlis, Mukhlis; Wulansari, Wulansari (Jurnal Pengabdian UNDIKMA, 2025)
This community service program aims to enhance the understanding and skills of farmer group members in conducting spatial-based data collection of sugar palm (Arenga pinnata) resources. The methods implemented include socialization, spatial data collection training using mobile GPS, participatory mapping assistance, and program evaluation through pre-test and post-test methods. Data analysis was carried out using GIS software. The results of the participatory mapping of sugar palm potential identified 36 potential points of Arenga pinnata within the operational area of the Karya Baru Farmer Group, consisting of 7 productive trees and 29 non-productive ones. Evaluation results indicated a significant improvement in participants’ competencies, with increases of 43.2% in skills, 41.8% in motivation, 37.3% in knowledge, and 33.9% in attitude—demonstrating the achievement and effectiveness of the participatory mapping program. Overall, the Participatory Mapping of Sugar Palm Potential activity in the Karya Baru Farmer Group area has successfully increased members’ understanding of the importance of mapping and recording natural resource assets as a foundational database for the future development of sugar palm–based products.